EFFECT OF ELECTROLYTE COMPOSITION ON THE STRUCTURE AND IR SPECTROSCOPIC PROPERTIES OF POROUS ANODIC ALUMINA - G. H. Knoernschild; A. A. Poznyak; V. A. Polubok (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A formation of anodic alumina in malonic acid containing complexing additives arsezano I and without it,the kinetics of the formation of alumina, mesoporous structure, Pilling-Bedworth ratio and solution study.